Performance Testing of The CNC Laser Engraver Machine on Plywood Media - Anrinal; Muhammad Fadherizal; Asmara Yanto (Jurnal Teknik Mesin, 2023)
This work aims to test and analyze the performance of the CNC Laser Engraver Machine on plywood media by using the grbl settings. The engraving process was conducted by using three filling methods in the grbl setting, i.e., reversed diagonal filling, horizontal filling and no filling. In the reversed diagonal filling method is tested a gears image input, in the horizontal filling method is tested a rumah gadang image input and in the no-filling method is tested a piston image input. The machine performance was assessed by comparing the CAD-based images input with the engraved images output that are carved on plywood media by a laser speed setting of 1000 mm/min, a laser power scale of 60% and a distance of laser from the media of 5 cm. From this assessment it can be concluded that the CNC Laser Engraver Machine is capable to create the shape and size of the images output that is the same as the shape and size of the images input. Here, the images size is obtained by a vernier caliper that has an accuracy of 0.05 mm.